Depression underdiagnosis in the primary healthcare: a study of patientes from the South-Western area of Santiago, during 2006 - Valdés, Gilda; Contreras, Ximena; Romero, William; Medina, Mariana; Norero, Blanca; Dussaillant, Catalina; Pérez, Ma. Victoria; Franzani, Andrés (Revista Chilena de Salud Pública, 2006)
Depression is highly prevalent in Chile. However, many patients are not detected by primary healthcare physicians (PHCP). The purpose of the present study is to analyze the consistency between the diagnosis of depression performed by PHCP, and diagnosis resulting from a structured clinical interview based on DSM-IV criteria (Diagnostic and Statistical Manual for Mental Disorders, IVth Edition) for depression, taking place at a secondary healthcare center (SHCC). A total of 174 patients were studied (mean age 57.6 15.1 years, 131 female), referred for various pathologies different from depression to one SHCC, and who had been assessed during the last month by a PHCP. All patients were assessed with the Goldberg's Anxiety and Depression Scale (GADS) and the probable cases determined to be so by the instrument used (a score 3 in depression scale subset) underwent a structured clinical interview based on the DSM-IV criteria for depression. Thirty three patients had a diagnosis of depression made by the PHCP. However, 103 (59.2%) had scores 3 in the GADS and 59, (33.9%) met the DSM-IV criteria for depression. The consistency between the diagnosis made by a PHCP and that made through the DSM-IV diagnostic criteria, assessed through Kappa index, was 0.39 (weakly consistent), with a positive consistency only in 25 cases. A low consistency was observed between the diagnosis of depression made by PHCP and the diagnosis reached through a structured clinical interview, with underdiagnosis being as relevant as nearly 60%. Additionally, the use of a screening test allowed the identification of cases not diagnosed previously.